Residue occurrence and potential risk assessment of HCHs and DDTs in campus surface soils: In case of Jilin University in Changchun, China. Issue 1 (October 2020) - Lu, Jilong; Zhao, Wei; Wei, Qiaoqiao; Hou, Yaru; Si, Junshi; Li, Tong; Zang, Libin
Abstract: Hexachlorocyclohexane(HCH) and Dichlorodiphenyltrichloroethane (DDT) are typical Organochlorine pesticides (OCPs), which were widely used in pest control and insect infestation in China. This study aimed at researching the concentration, potential sources and potential risk of HCH and DDT in Jilin University in Changchun, China. A total of 45 surface soil samples were collected from five land-use types in Jilin University campuses, the contents of were determined by Gas Chromatography and Mass Spectrometry (GC-MS) with Soxhlet extraction pretreatment technology. The overall HCHs existed the pollution in some campuses, while the DDTs were relatively low without pollution. Results of composition analysis showed that HCHs in campus soils mainly came from the mixed use of technical HCHs and lindane, and DDTs were mainly from the input of historical dicofol products. The potential health risks of HCHs and DDTs to campus populations were very low, while the potential ecological risks of HCHs and DDTs individual isomers should be paid attentions to.